2019
DOI: 10.1371/journal.pgen.1007439
|View full text |Cite
|
Sign up to set email alerts
|

Transition from a meiotic to a somatic-like DNA damage response during the pachytene stage in mouse meiosis

Abstract: Homologous recombination (HR) is the principal mechanism of DNA repair acting during meiosis and is fundamental for the segregation of chromosomes and the increase of genetic diversity. Nevertheless, non-homologous end joining (NHEJ) mechanisms can also act during meiosis, mainly in response to exogenously-induced DNA damage in late stages of first meiotic prophase. In order to better understand the relationship between these two repair pathways, we studied the response to DNA damage during male mouse meiosis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 99 publications
1
62
1
Order By: Relevance
“…Further, it was previously shown that MEILB2/HSF2BP persisted in pahytene (Zhang et al, 2019). It was demonstrated that early meiotic repair pathway that acts by default at the beginning of meiotic prophase is replaced sequentially by non-homologous end joining (NHEJ) and somatic-like homologous recombination (HR) pathway involving RAD51 (Enguita-Marruedo et al, 2019). Although we do not yet know the biological relevance of the detectable MRM foci in late meiotic prophase, MRM may be involved in "somatic-like HR repair pathway" in that stage.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was previously shown that MEILB2/HSF2BP persisted in pahytene (Zhang et al, 2019). It was demonstrated that early meiotic repair pathway that acts by default at the beginning of meiotic prophase is replaced sequentially by non-homologous end joining (NHEJ) and somatic-like homologous recombination (HR) pathway involving RAD51 (Enguita-Marruedo et al, 2019). Although we do not yet know the biological relevance of the detectable MRM foci in late meiotic prophase, MRM may be involved in "somatic-like HR repair pathway" in that stage.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the enrichment of C>G mutations stems from a switch in the repair machinery late in meiosis (78-80); DSBs still not repaired by this stage may be repaired by a more mitotic-like repair pathway, which could potentially be more mutagenic (80,81). Notably, the source of the C>G signature found by Jónsson et al, 2017 in specific autosomal regions could also be late repair; indeed, if these areas reflect damage, as the authors surmise, they may only undergo repair later in meiosis.…”
Section: Accidental and A Subset Of Meiotic Double-strand Breaks In Tmentioning
confidence: 99%
“…While repair of DSBs in meiosis occurs exclusively via HR pathway components, 53BP1 is associated primarily with the non-homologous end joining (NHEJ) DSB repair pathway. Therefore, its activity as a DSB responsive element may be down-regulated during early meiosis (Enguita-Marruedo et al, 2019), resulting in less 53BP1-based reporter foci detection in the female germ cells at this time.…”
Section: Radiation-induced Reporter Foci Dynamics Differ Between Malementioning
confidence: 99%